2020
DOI: 10.1136/annrheumdis-2019-216374
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the serum metabolome and lipidome identify potential biomarkers for seronegative rheumatoid arthritis versus psoriatic arthritis

Abstract: ObjectivesThe differential diagnosis of seronegative rheumatoid arthritis (negRA) and psoriasis arthritis (PsA) is often difficult due to the similarity of symptoms and the unavailability of reliable clinical markers. Since chronic inflammation induces major changes in the serum metabolome and lipidome, we tested whether differences in serum metabolites and lipids could aid in improving the differential diagnosis of these diseases.MethodsSera from negRA and PsA patients with established diagnosis were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 51 publications
(56 reference statements)
4
88
0
1
Order By: Relevance
“…Finally, oxylipin profiling led us to identify differences between seronegative and seropositive RA. Although previous metabolomics studies have shown distinct metabolomic signatures in seronegative RA patients, the exact compounds have not been elucidated (49). Our results confirm that whereas both subsets could be distinguished from controls based on oxylipin signatures, the precursors and pathways greatly differed between them.…”
Section: Discussionsupporting
confidence: 76%
“…Finally, oxylipin profiling led us to identify differences between seronegative and seropositive RA. Although previous metabolomics studies have shown distinct metabolomic signatures in seronegative RA patients, the exact compounds have not been elucidated (49). Our results confirm that whereas both subsets could be distinguished from controls based on oxylipin signatures, the precursors and pathways greatly differed between them.…”
Section: Discussionsupporting
confidence: 76%
“…For starters, the use of well-accepted standardized food intake surveys in future metabolomics studies may give a handle on this variable. ► The above recommendations apply not only to metabolomics studies in SLE, but also to similar investigations in other rheumatic diseases such as rheumatoid arthritis and primary Sjögren’s syndrome, where these same confounding factors have been consistently overlooked [ 65 – 72 ]. …”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Our RA patients with US at synovitis, most of them RF and ACPA-, showed lower levels of serum biomarkers, resembling PsA patients [30]. Therefore, sero-RA could represent a different entity, standing between sero + RA and PsA, as it has also been suggested in recent studies analyzing serum metabolomes and lipidomes [31].…”
Section: Discussionmentioning
confidence: 72%